2010
DOI: 10.1177/0275074010373803
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Social Networks in Affective Organizational Commitment: Network Centrality, Strength of Ties, and Structural Holes

Abstract: Although studies in public management have identified personal attributes, job characteristics, and organizational rewards as key factors that influence affective organizational commitment, limited attention has been paid to the influence of social networks on affective commitment. Given that organizational attitudes and behaviors are often socially constructed, this article argues that employees’ affective commitment is influenced by their social networks in an organization. What are the social network config… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 66 publications
(104 reference statements)
5
64
1
1
Order By: Relevance
“…Research has shown that the key factors shaping commitment are: superior coaching, properly provided feedback, the type of control and social support felt by the employee (Bakker, Demerouti, 2008;Halbesleben, 2010). Research conducted by different authors in public sector organisations has confirmed a positive relationship between HRM practices, including career opportunities, participation in training programmes and promotion prospects, and affective commitment (Kooij, et al, 2010;Lee, Kim, 2011).…”
Section: The Role Of the Hrm System In Building Commitment And Trustmentioning
confidence: 96%
“…Research has shown that the key factors shaping commitment are: superior coaching, properly provided feedback, the type of control and social support felt by the employee (Bakker, Demerouti, 2008;Halbesleben, 2010). Research conducted by different authors in public sector organisations has confirmed a positive relationship between HRM practices, including career opportunities, participation in training programmes and promotion prospects, and affective commitment (Kooij, et al, 2010;Lee, Kim, 2011).…”
Section: The Role Of the Hrm System In Building Commitment And Trustmentioning
confidence: 96%
“…It is used both as a metaphor to describe and explain intergovernmental, cross-sector, interorganizational relationships (Koliba et al, 2010) and as methodological tools to examine relational data (Choi and Kim, 2007;Kapucu and Demiroz, 2011;Lee and Kim, 2011). Networks have been applied in many areas and different contexts (Jasny, 2012;Lee et al, 2012;Provan and Huang, 2012;Schalk et al, 2010).…”
Section: Research On Network Performancementioning
confidence: 99%
“…The article utilizes the network approach for analysis and evaluation purposes. Network analysis has been 10 Administration & Society suggested as a useful tool to examine the structural and relational aspects of networks (Kapucu, 2006a;J. Lee & Kim, 2011;Milward & Provan, 1998).…”
Section: Network Structure and Performancementioning
confidence: 99%